Comparison of glycosylated hemoglobin levels in periodontitis patients and healthy controls: A pilot study in Indian population - Ruchika M Saxena; P C Deepika (Wolters Kluwer Medknow Publications, 2012)
Background: Periodontitis is associated with glycemic control in patients with diabetes. The purpose of this study was to determine if glycosylated hemoglobin is elevated in patients with periodontitis who are non-diabetic adults. Materials and Methods: A total of 36 patients were selected and were divided into test and control groups. Test group included 18 adults without diabetes, but with periodontitis (having at least five teeth with probing depth (PD) ≥5 mm, bleeding on probing (BOP), and clinical attachment loss (>1 mm) on >5 teeth or radiographic bone loss), and the control group included 18 healthy adults (PDs ≤4 mm and BOP ≤15% and no clinical attachment loss). Glycosylated hemoglobin (HbA1c) was assessed in laboratory for these patients. Groups were compared using the t test,kruskal-wallis test, pearsson correlation. Results: Both the groups showed similar HbA1c levels, but there was a marginal increase in levels in the test group (cases), which was not statistically significant (cases- 6.06%, controls-5.8%; P=0.101).There was no significant difference found in the mean HbA1c levels among males and females and among various age groups. Mean BMI among the cases and controls was found to be similar. When inter and intra group comparisons were done according to BMI categories among the cases and controls, we found similar mean HbA1c values. Conclusion: Indians are at a high risk of developing periodontitis and diabetes. These data suggest a possible link between periodontitis and glycemic control in non-diabetic individuals. Periodontal disease may be a potential contributor to development of type 2 diabetes.